RATE OF SUCCESSFUL ATTEMPTS OF MALE WEIGHTLIFTERS ON THE 2024 EUROPEAN WEIGHTLIFTING CHAMPIONSHIPS - V. Panayotov; N. Yankova (Trakia Journal of Sciences)
The results in official competitions is a valuable source of feedback information for coaches and sports scientists to successfully control the training process. In international tournaments, elite athletes are often under tremendous psychological and physiological pressure to achieve great performance. In Olympic weightlifting, in events where athletes of similar potential and preparedness compete, the struggle for top places is especially intense, as often the final ranking depends on only one successful attempt. Unsuccessful attempts due to over-excitement are the most common reason competitors underperform or drop out. Purpose. The purpose of the study was to evaluate the rate of successful attempts of male weightlifters on the 2024 European weightlifting championships in Sofia, Bulgaria. Methods. The attempts of 170 male weightlifters in 10 weight classes were recorded and statistically analyzed. The rate of successful attempts was estimated –overall and stratified by attempt number.Results. The overall rate of successful attempts for the snatch and clean and jerk was similar (with insignificant differences) for all studied weight classes. For both competitive exercises, the highest success rate was measured in the first attempts, followed by second and third. 52% of the attempts in the snatch were successful compared with only 47% in the clean and jerk. Conclusion.In our opinion, pre-competition reduction of body mass and/or accumulated fatigue during the preparation is the main reason for this 6% statistically significant difference. As the snatch is the more technical exercise than the clean and jerk, these findings may be due to strictly methodological reasons: Early specialization is typical for Olympic weightlifting –during their first years in the sport, athletes place an emphasis on developing proper technique at the expense of strength work.